The Effectiveness of Drug Use and Acquired Immune Deficiency Syndrome (AIDS) Prevention Package on Drug Use and High Risk Behaviors Reduction Among College Students - Masoumeh Behboodi; Mohsen Ahmadi Tahoor Soltani (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: With the onset of adulthood, the rate of high-risk behaviors in individuals rises. Research has shown that preventive training schedules reduces the incidence of high-risk behaviors. The purpose of this study was to investigate Effectiveness of Drug Use and Acquired Immune Deficiency Syndrome (AIDS) Prevention Package on Drug Use and High Risk Behaviors Reduction among College Students of Islamic Azad University, Roudehen Branch. Methods: The study sample was composed of all students in different grades. The sampling method of research had two stages. First, 384 students were selected according to Krejcie and Morgan chart, using stratified random sampling method; they answered to Risky Behaviors questionnaire. Then 15 participants were randomly assigned to the experimental group and 15 participants to the control group. Using risky behavior questionnaire a pre-test was performed for both groups. Then the experimental group participated in 12 session (each session 90 minutes) of drug use and Acquired Immune Deficiency Syndrome prevention workshop; the control group remained on a waiting list. At the end of training sessions and one month follow up, both groups were tested again. Data was analyzed using repeated measures design. Results: The results showed that the variable scores of tendency to drug use, sexual risk behaviors, anti-social behavior and suicidal thoughts in the post-test and follow-up in experimental group was significantly lower than the control group. So we can conclude that the training package of drug use and AIDS prevention and prevention is effective in drug use and risky behavior reduction. Conclusion: It can be concluded that the drug use and acquired immune deficiency syndrome Prevention Package can be effective in reducing drug use and high-risk behaviors.